Cytogeography of Pilosella officinarum (Compositae): altitudinal and longitudinal differences in ploidy level distribution in the Czech Republic and Slovakia and the general pattern in Europe - Mráz, Patrik; Singliarová, Barbora; Urfus, Tomás; Krahulec, Frantisek (Annals of botany, 2008)
BACKGROUND AND AIMS: Pilosella officinarum (syn. Hieracium pilosella) is a highly structured species with respect to the ploidy level, with obvious cytogeographic trends. Previous non-collated data indicated a possible differentiation in the frequency of particular ploidy levels in the Czech Republic and Slovakia. Therefore, detailed sampling and ploidy level analyses were assessed to reveal a boundary of common occurrence of tetraploids on one hand and higher ploids on the other. For a better understanding of cytogeographic differentiation of P. officinarum in central Europe, a search was made for a general cytogeographic pattern in Europe based on published data. METHODS: DNA-ploidy level and/or chromosome number were identified for 1059 plants using flow cytometry and/or chromosome counting on root meristem preparations. Samples were collected from 336 localities in the Czech Republic, Slovakia and north-eastern Hungary. In addition, ploidy levels were determined for plants from 18 localities in Bulgaria, Georgia, Ireland, Italy, Romania and Ukraine. KEY RESULTS: Four ploidy levels were found in the studied area with a contrasting pattern of distribution. The most widespread cytotype in the western part of the Czech Republic is tetraploid (4x) reproducing sexually, while the apomictic pentaploids and mostly apomictic hexaploids (5x and 6x, respectively) clearly prevail in Slovakia and the eastern part of the Czech Republic. The boundary between common occurrence of tetraploids and higher ploids is very obvious and represents the geomorphologic boundary between the Bohemian Massif and the Western Carpathians with the adjacent part of Pannonia. Mixed populations consisting of two different ploidy levels were recorded in nearly 11% of localities. A statistically significant difference in a vertical distribution of penta- and hexaploids was observed in the Western Carpathians and the adjacent Pannonian Plain. Hexaploid populations tend to occur at lower elevations (usually below 500 m), while the pentaploid level is more or less evenly distributed up to 1000 m a.s.l. For the first time the heptaploid level (7x) was found on one site in Slovakia. In Europe, the sexual tetraploid level has clearly a sub-Atlantic character of distribution. The plants of higher ploidy level (penta- and hexa-) with mostly apomictic reproduction prevail in the northern part of Scandinavia and the British Isles, the Alps and the Western Carpathians with the adjacent part of Pannonia. A detailed overview of published data shows that extremely rare records on existence of diploid populations in the south-west Alps are with high probability erroneous and most probably refer to the closely related diploid species P. peleteriana. CONCLUSIONS: The recent distribution of P. officinarum in Europe is complex and probably reflects the climatic changes during the Pleistocene and consequent postglacial migrations. Probably both penta- and hexaploids arose independently in central Europe (Alps and Carpathian Mountains) and in northern Europe (Scandinavia, Great Britain, Ireland), where the apomictic plants colonized deglaciated areas. We suggest that P. officinarum is in fact an amphidiploid species with a basic tetraploid level, which probably originated from hybridizations of diploid taxa from the section Pilosellina.
Keywords: Asteraceae; Slovenská republika; Geography; genetická variace; Genetic Variation; průtoková cytometrie; Ploidies; Reproduction; zeměpis; ploidie; Česká republika; rozmnožování; Flow Cytometry; Europe; Evropa; Czech Republic; Slovakia